Services quality: Implications for Management in Higher Education from the perspective of the disable - Hamedon, Siti Rohimi; Nik Idris, Nik Ruzni; Abdullah, Nur Anisah; Saad, Nurulwahida (2012)
Recent societal changes and recognition of the importance of having good quality services in higher education have pushed the issues to the top of the research agenda within higher education sectors. The notion of the incompatibility of service quality and higher education is changing fast in Malaysia. Stakeholders are becoming more discriminating in selecting institution of higher learning. A group of stakeholders are students with different abilities. Their perceptions of services quality are different so as to meet their different needs. This paper examines the perception of on services quality. The focus is on academic services quality and facilities services quality. Data was collected via Focus Group Discussions. Interview transcripts were analyzed by Thematic analysis Method. In this paper the author identifies potential list of areas for improvement surrounding management processes at various levels to support policy review and development in higher education institution.